Vimal Logo - Reliance Industries Limited (2023)
A logo of the Vimal brand, that was launched by Shri Dhirubhai Ambani in the late 1960s. It was named after Shri Dhirubhai Ambani's brother Ramnikbhai's son, Vimal Ambani.